Modelo de otimização de processos para melhoria da qualidade dos serviços em uma Instituição de ensino público - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The quality since the advent of globalization has become one of the keywords most widespread in society. In the public sector is associated to the rapidity, reliability, precision and security, however, the general perception that the individuals have on the provision of public services in Brazil is not consistent with these adjectives quality. The literature suggests several tools to evaluate and improve the quality in services, but is subjective mechanisms predominate, which are summed to measure customer satisfaction. Admittedly, the quality has focused on the customer, but in the current Era of Quality is assumed that it is generated in the production process. Considering this gap, the question arose: how to optimize processes of the service sector, while focusing on quality improvement, especially processes executed in the public sector of education? To answer this question, it was adapted a model of analysis and processes improvement through the concatenation phases of Method of Analysis and Solution of Problems (MASP) with the phases of Design of Experiments. It was applied the proposed model in the Coordination of Integration Business-School (CIE-E) of IFAM Campus Manaus Donwtown, evaluating 397 records of stages finalized in the year 2012, where the duration of the process was portrayed as the villain. Thus, it was developed an experimental research characterized as exploratory and descriptive in nature and applied qualitative and quantitative approach. It was used Quality Tools for collection and evaluation of the data, as well the Nonparametric Tests for data analysis. Finally, supported on quality criteria and statistician identified that the combination high time load and no labour experience was the ideal combination of controllable factors that interfered in the records stage studied, resulting in lower process time, ie, it determined the optimal region. Thus, with this study, we evaluated the implantation procedure of statistical techniques in the service sector for the optimization and improvement of its processes.
Keywords: Qualidade; Setor de Serviço; Otimização de Processos; Testes de Hipóteses.; Quality; Service Sector; Process Optimization, Hypothesis Testing.; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO